Balanced use of agricultural land affected by war in Ukraine as a prerequisite for sustainable development - Bavrovska, N.; Koshel, A.; Tykhenko, O. (Land Management, Cadastre and Land Monitoring, 2024)
The issue of ensuring the sustainable development of humanity is recognized as one of the most urgent problems facing society today. The article is devoted to the generalization of the features of the development of sustainable land use and the definition of the main problems of the sustainable use of agricultural land in Ukraine during the period of European integration, reforms of local self-government in the country, martial law and post-war recovery. The work highlights the main principles and goals of sustainable land use, in accordance with the concept of sustainable development. According to the authors, the practical implementation of the concept of sustainable land use requires determining the priorities of the use of agricultural land, and above all, ecological land. It was noted that the state of land resources in Ukraine was characterized as tense, due to the irrational use of the country’s land resource potential, excessive plowing and land degradation. The authors note that organic agriculture has been developing in Ukraine in recent decades, but as a result of full-scale Russian aggression against Ukraine in 2022, the issue of organic production in Ukraine took a back seat. The most acute environmental problems are the development of degradation processes on the arable lands of Ukraine, which causes the mining of territories, the formation of craters from shelling, and landslides. Proposed priority areas of development of sustainable land use in Ukraine, which will allow transition to a model of sustainable development